Importance of research in the approach to reading experiences: teachers’ and students’ narratives - Mateus Ojeda, Carmen Helena; Cristancho Carvajal, Viviana Paola; Rojas Romero, Camila Fernanda; Rodríguez Vargas, Gabriel Santiago; Romero Alfonso, Sonia Lucía (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The investigation points to a reality inside Institución Educativa in front of the reading process of First grade and Second grade students, that process makes a fundamental curiosity in researchers, creating a challenge for those who have interest in rethinking and redirecting children’s formation, presenting the importance of the experiences which have been faced by the kids in this process, in addition to this, the environment features are recognized inside the institution in regards to the teacher practices that are done in there. It constitutes a compendium of experiences and reading experiences of children, having reading as its main theme, supported by authors who describe the theoretical concept of this category of research, in which the educational activity is developed describing in detail the reading process that It is carried out in the Liceo Colombo Inglés Educational Institution of the municipality of Chiquinquirá, starting from the analysis of the reading experiences of the children taking into account the teaching practices and the importance of research for the teacher, remembering at the same time that the autobiography is the main analysis instrument regarding the process of experiences provided by children in their approach to reading.